ANALISIS SWOT SD YANG MEMILIKI EKSTRAKURIKULER PRAMUKA SAJA DALAM RANGKA PENGEMBANGAN POTENSI ANAK SD - Indri Januari Nurjanah; Muhammad Luthfi Setyawan Anshory; Nita Oktaviani; Agus Mulyana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
SWOT analysis is an evaluation method used to evaluate strengths (Straight), weaknesses (Weeknesses), opportunities (Opportunities) and threats (Threats) in a project or organization. Extracurricular activities that often occur to someone refer to activities or programs outside the main curriculum in an educational institution at school, usually including religious activities, sports, arts and so on. The potential of elementary school children usually includes all the talents, positive characteristics and abilities possessed by an elementary school student. This research aims to carry out a SWOT analysis of elementary or elementary schools that focus on developing children's potential through just one extracurricular owned by the school. This research method involves collecting qualitative data from elementary schools that have limited extracurricular activities. The results of the analysis show that elementary schools have strengths in their teachers' commitment to developing children's potential, but have weaknesses which lie in the lack of variety of extracurriculars offered, but still have opportunities where these extracurriculars can be developed and collaborate with outside parties and even gain many achievements from activities. However, extracurricular activities are limited, but we need to remember that there are threats that come from a lack of financial support. Based on these friends, the researcher recommends that these limited extracurricular activities can still be developed more optimally with the help of external parties and maximum cooperation and if possible extracurricular activities need to be added. It is hoped that this research can contribute to the development of education, especially at the elementary school level and can maximize children's potential through a measurable and sustainable extracurricular approach.